Personal financial planning in Poland against the background of international experience - Waliszewski, Krzysztof (Planowanie finansów osobistych w Polsce na tle doświadczeń międzynarodowych, 2014)
The objective of this article is to present a profession personal financial advisor in Poland against the background of an international perspective ( the USA, the United Kingdom and the EU). The main hypothesis of this article is as follows: personal financial planning in Poland is developing area and its role will be growing in the future, especially in the pension, investment, insurance and credits area, but this growth will depend on the growth of economic and financial literacy, the enrichment of Polish society and the creation of public confidence towards the personal financial advisor profession. The auxiliary hypothesis of the article is as follows: the main barriers in the development of the financial advisor profession in Poland are low financial knowledge/financial literacy, lack of awareness in the benefits of personal financial planning and advising, reluctance to pay for professional financial advice, low savings rate and lack of regular savings habit and the low level of advice services’ market regulation. Verification of the hypothesis will base on literature study and own study executed among independent personal financial advisors
Nauki o Finansach = Financial Sciences, 2014, Nr 4 (21), s. 111-134
Keywords: personal finance; household finance; financial literacy; financial advisor; finanse osobiste; finanse gospodarstw domowych; inteligencja finansowa; doradca finansowy